Hambatan Penerapan Sistem Informasi Rumah Sakit Terkait Statistik di RSU PKU Muhammadiyah Bantul - ISTIQLAL, Achmad Reza Nuzul ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: In middle August 2012 for a change of SIRS, SIRS not yet completed in the making, especially on the statistics, but it has been applied in the hospital. It inhibits the hospital internal reporting statistics related to RSU PKU Muhammadiyah Bantul. Making internal reports related hospital hampered statistical calculations of data contained on BTO, GDR, and NDR. As a result of the lack of data calculation is done manually by medical records personnel section so SIRS related statistics do not support the work process to the fullest. Thus, in this study researchers evaluated the obstacles that exist in the application of SIRS related statistics can know what obstacles are there to be followed up further. Objective: This study aimed to determine the use of SIRS related statistics, and determine the factors causing the obstacles to the use of statistics based on human resources, hardware, software and LAN networks. Methods: The research method was descriptive and qualitative approach using cross-sectional design. Study subjects consisted of medical records personnel and EDP officers. Object of this study was SIRS related statistically in RSU PKU Muhammadiyah Bantul. Results: The results of medical record personnel are involved and the statistical part can be the use of SIRS associated with doing statistical processing of data for hospital statistical reporting. Factors causing obstacle to the use of SIRS related statistics are software that can not help the process of the task and the lack of transition in the use of SIRS, and the absence of a LAN network maintenance done regularly.